Pengaruh Beban Kerja dan Stres Kerja terhadap Kinerja Perawat melalui Kualitas Pelayanan Keperawatan di Puskesmas Bluto, Kabupaten Sumenep - Kartono Kartono,; Rusdiyanto Rusdiyanto,; Woro Utari, (Journal of Management and Creative Business, 2025)
This study aims to analyze the effect of workload and work stress on nurse performance by considering the role of nursing service quality as a mediating variable. The study was conducted at the Bluto Health Center, Sumenep Regency, which is one of the first-level public health service centers in the area. The research method used a quantitative approach with an explanatory design. A total of 37 nurses became research respondents. Data were collected through structured questionnaires and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) technique. The results showed that workload had a significant positive effect on the quality of nursing services (coefficient 0.461; p = 0.001) and nurse performance (coefficient 0.343; p = 0.003). Conversely, work stress had a significant negative impact on the quality of nursing services (coefficient -0.362; p = 0.02) but did not have a significant direct effect on nurse performance (coefficient -0.129; p = 0.290). In addition, the quality of nursing services is proven to have a significant positive effect on nurse performance (coefficient 0.526; p = 0.000). Furthermore, the quality of nursing services is proven to mediate the relationship between workload and work stress on performance. Workload increases performance through service quality (coefficient 0.243; p = 0.020), while work stress decreases performance through the same pathway (coefficient -0.191; p = 0.040). This study emphasizes the importance of managing workload and stress to improve nurse performance through improving the quality of nursing services.